2018
DOI: 10.1093/toxsci/kfy303
|View full text |Cite
|
Sign up to set email alerts
|

Placental BCRP/ABCG2Transporter Prevents Fetal Exposure to the Estrogenic Mycotoxin Zearalenone

Abstract: In the placenta, the breast cancer resistance protein (BCRP)/ABCG2 efflux transporter limits the maternal-to-fetal transfer of drugs and chemicals. Previous research has pointed to the estrogenic mycotoxin zearalenone as a potential substrate for BCRP. Here, we sought to assess the role of the BCRP transporter in the transplacental disposition of zearalenone during pregnancy. In vitro transwell transport assays employing BCRP/Bcrp-transfected Madine-Darby canine kidney cells and BeWo trophoblasts with reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In addition, the estrogenic mycotoxin zearalenone was first described as an ABCG2 substrate by Xiao et al [66], who observed decreased intracellular accumulation as well as increased resistance to the cytotoxicity mediated by this compound in ABCG2 -overexpressing cells. The same research group later confirmed the specific involvement of murine and human ABCG2 in bidirectional transport assays and revealed that foetal exposure to this mycotoxin was increased in Abcg2- knockout mice [145]. Murine and human ABCG2 is also involved in the efflux of the mycotoxin ochratoxin A in cell culture models [84].…”
Section: Transporters With Increased Expression In Lactating Mammamentioning
confidence: 99%
“…In addition, the estrogenic mycotoxin zearalenone was first described as an ABCG2 substrate by Xiao et al [66], who observed decreased intracellular accumulation as well as increased resistance to the cytotoxicity mediated by this compound in ABCG2 -overexpressing cells. The same research group later confirmed the specific involvement of murine and human ABCG2 in bidirectional transport assays and revealed that foetal exposure to this mycotoxin was increased in Abcg2- knockout mice [145]. Murine and human ABCG2 is also involved in the efflux of the mycotoxin ochratoxin A in cell culture models [84].…”
Section: Transporters With Increased Expression In Lactating Mammamentioning
confidence: 99%
“…However, no effects were observed in ICompetent animals at a low ZIKV titer or in Abcg1 in any experimental setting. As such, ZIKV also likely increases the fetal accumulation of Bcrp substrates (antibiotics, antiretrovirals, sulfonylureas, folate, mercuric species, estrogenic mycotoxins, carcinogens phototoxic compounds, among others) and disrupts placental lipid homeostasis (lipids, cholesterol, cytotoxic oxysterols) by reducing placental Abca1 expression(25,(66)(67)(68)(69).…”
mentioning
confidence: 99%
“…In the pharmacological and toxicological context, results obtained at GD15.5 suggest that LPS-induced upregulation of Bcrp in the amnion facing-mesothelium, favors the entry of Bcrp substrates into the embryo/fetal compartment. In this context, Bcrp substrates of clinical importance comprise 1) xenobiotics: including antibiotics, antiretrovirals, sulfonylureas, nonsteroidal anti-inflammatory drugs (NSAIDs), proton pump inhibitors (PPIs), and 2) toxicants : including select mercuric species, estrogenic mycotoxins, carcinogens phototoxic compounds [ 19 , [28] , [29] , [30] , [31] ]. We have previously demonstrated a decrease in placental Bcrp expression in mice exposed to LPS in the same experimental design and dose regimens [ 32 ].…”
Section: Discussionmentioning
confidence: 99%